Oral vascular lesions: clinical, diagnostic and therapeutic evaluations - Marcelo Gadelha Vasconcelos; Lucas Emmanuell Morais Neves; Ana Karoline Vieira Melo; Rodrigo Gadelha Rodrigo (Editorial Ciencias Médicas, 2018)
Introduction: Vascular disorders affect the head and neck regions with high incidence. When they affect the oral region, there is a predilection for lips, tongue and mouth commissure, predominantly in the female. Objective: To analyze oral vascular lesions, emphasizing the clinical characteristics, diagnostic methods and therapeutic approach. Methods: A bibliographic review was carried out in the databases PubMED/Medline, Lilacs, Science Direct andSciELO (Scientific Electronic Library). We used the descriptors hemangioma, vascular malformations, sclerotherapy and photocoagulation, in Portuguese, English and Spanish. We obtained 262 complete articles, of which 18 were used as appropriate scientific basis for this topic, based on the inclusion and exclusion criteria. Results: Oral vascular lesions are clinically characterized as single lesions of the nodes or blotches, whose color varies from deep red to purple and are of variable size. In order to diagnose these lesions, clinical examinations associated with the periodontal disease are commonly used, although in most cases they do not require complementary examinations. The therapeutic intervention is justified due to aesthetic deformities, possible bleeding, ulcerations and infections. For such changes, there are several therapeutic modalities, including sclerotherapy, cryotherapy, surgical removal and laser photocoagulation therapy. Conclusions: Oral vascular lesions show peculiar clinical characteristics, presenting as nodules or spots, whose coloration varies from intense red to purple. Diascopy is the most used and reliable semi-technical method for establishing the clinical diagnosis of these lesions. The use of sclerosing solutions is the most described treatment in the literature, followed by laser photocoagulation.